Improving Learning Performance Through Evaluation of the Free Nutritional Meal Program in Schools - M. Rizki Arobi; Aris Munandar; Irfan Pratama; Fia Lestari; Eva Wulandari; Sulistyawati Pohan; Veni Ayu Aprilia; Zulma Aprila (Al-Qalam Institue, 2025)
Education in Indonesia faces significant challenges related to student nutritional needs, which impact concentration and motivation to learn. The Free Nutritional Meal Program (MBG) at Ahmad Dahlan Junior High School in Jambi City aims to improve student nutritional status and support learning. This study aims to evaluate the impact of the MBG Program on student learning quality, focusing on concentration, motivation, and engagement. The method used was a qualitative case study approach, involving observation, interviews, and documentation. The results showed that the MBG Program had a positive impact on student concentration and attendance, but faced challenges related to menu incompatibility with student preferences and issues with hygiene and food quality. Menu adjustments and hygiene monitoring are crucial to improve the program's effectiveness. This study contributes to understanding how nutrition programs can support learning. It emphasizes the importance of menu adjustments and regular evaluation in improving the success of similar programs in the future.